The Effect of Latent Toxoplasma gondii Infection on the Immune Response in HIV-Infected Patients. (12th July 2015) - Beran, Ondrej; Kodym, Petr; Maly, Marek; Davidova, Alzbeta; Reinvartova, Gabriela; Jilich, David; Holub, Michal; Rozsypal, Hanus
Abstract : A relationship between latent toxoplasmosis and the immune system during HIV disease is poorly understood. Therefore, the aim of this follow-up study was to characterize immunological parameters in HIV-infected patients with latent toxoplasmosis and noninfected individuals. A total of 101 HIV-infected patients were enrolled in the study. The patients were classified into two groups based on anti- Toxoplasma gondii antibodies: a group of 55 toxoplasma-positive persons (TP) and a group of 46 toxoplasma-negative persons (TN). Absolute counts of several lymphocyte subsets decreased in the TP group, namely, T cells (p = 0.007 ), B cells (p = 0.002 ), NK cells (p = 0.009 ), CD4 T cells (p = 0.028 ), and CD8 T cells (p = 0.004 ). On the other hand, the percentage of CD8 T cells expressing CD38 and HLA-DR significantly increased during the follow-up in the TP group (p = 0.003, p = 0.042, resp.) as well as the intensity of CD38 and HLA-DR expression (MFI) on CD8 T cells (p = 0.001, p = 0.057, resp.). In the TN group, analysis of the kinetics of immunological parameters revealed no significant changes over time. In conclusion, the results suggest that latent T. gondii infection modulates the immune response during HIV infection.